Activation of mitogen activated protein kinase (MAPK) pathways after soman poisoning in rat cerebellar granule neurons - Pejchal, J; Osterreicher, J; Kassa, J; Tichý, A; Mokrý, J (Journal of applied toxicology, 2008)
The expression of activated p38 mitogen-activated protein kinase (MAPK) and activated MAPK transcription factors c-jun, c-myc and elk-1 were examined in rat cerebellum after soman poisoning to determine the pathogenetic mechanism of the non-specific long-term effects of nerve agents. Male Wistar rats were poisoned by intramuscular administration of soman at a dose 60 microg kg(-1) (70% LD(50)) and samples were taken 1, 7 and 14 days after poisoning, immunohistochemically stained and p-p38MAPK, p-c-jun, p-c-myc and p-elk-1 expressions were measured using image analysis. Control groups were administered with saline instead of soman. The expression of activated p38MAPK and c-myc increased 14 days after soman poisoning while c-jun and elk-1 expressions remained unchanged 1, 7 and 14 days after soman poisoning. Delayed activation of p38 MAPK and its targets might be involved in the pathogenetic mechanism of the long-term neurophysiological toxic effects of nerve agents.
Keywords: krysa rodu Rattus; mužské pohlaví; Neurons; Signal Transduction; Male; Immunohistochemistry; Chemical Warfare Agents; Proto-Oncogene Proteins c-jun; Image Processing, Computer-Assisted; počítačové zpracování obrazu; imunohistochemie; Rats; aktivace enzymů; p38 Mitogen-Activated Protein Kinases; Enzyme Activation; soman; potkani Wistar; Cerebellum; cytoplazmatická granula; signální transdukce; protoonkogenní proteiny c-jun; Soman; Animals; mozeček; zvířata; neurony; Proto-Oncogene Proteins c-myc; Rats, Wistar; chemické bojové látky; mitogenem aktivované proteinkinasy p38; Mitogen-Activated Protein Kinases; mitogenem aktivované proteinkinasy; Cytoplasmic Granules; protoonkogenní proteiny c-myc